The Effect of Tourist Attractions and Facilities on Visitor Satisfaction in Pasir Putih Situbondo Regency - Muh Hamdi Zain; Nina Fitriyah; Dewi Intan Fajria Fajria; Silsilatul Faida (POLITICO, 2025)
Coastal tourism in Indonesia, as an important sector in the tourism industry, contributes significantly to the national economy. However, even though White Sand Beach has great potential, the number of tourist visits is still low. This study aims to analyze the influence of tourist attractions and facilities on tourist visits. Purpose. The objectives of this study are to: 1. Analyze the influence of tourist attractions on the level of tourist visits. 2. Analyze the influence of tourist facilities on the level of tourist visits. 3. Analyze the simultaneous influence of tourist attractions and facilities on tourist visits. Methodology. The method used in this study is quantitative with a survey design. Data was collected through a questionnaire distributed to visitors to White Sand Beach. Data analysis was carried out using multiple linear regression to test the hypothesis that had been established. Findings. The results of the study show that: 1. Tourist attractions have a significant effect on the level of tourist visits. The natural beauty and tourist activities offered are the main motivation for visitors. 2. Tourist facilities also have a significant effect on the level of visits. Adequate facilities increase the comfort and satisfaction of visitors. 3. Simultaneously, tourist attractions and facilities have a significant influence on the level of visits.